(untitled) (International journal of artificial intelligence, 2025)
This article highlights the economic and ecological importance of rational use of land resources. It provides information on the current state of land resources, ways of their conservation and effective management, as well as environmental protection measures. The article also provides proposals and recommendations aimed at maintaining ecological balance, preventing land degradation and ensuring sustainable development. It is emphasized that the proper use of land resources is an important factor not only in the development of agriculture, but also in environmental protection.